Urea : Manfaat Pada Ruminansia - yanuartono - yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Hary Purnamaningsih; Slamet Rahardjo (Faculty of Animal Science, Universitas Brawijaya, 2018)
The problems of ruminant feeding have received considerable attention in the tropics. In the tropics, most ruminants are fed on low-quality roughages, agricultural crop-residues and industrial byproducts. Urea is widely available and has been used as a source of ammoniation to improve the feeding value of various grasses and crop residues. Furthermore, urea treatment as a supplement is relatively easy to apply, handling, inexpensive and valuable substitute for natural proteins in the ration. Although the use of urea has potential economic advantages for N sources, there are limitations and disadvantages to its use. Excess level of urea feeding may develop a problem of urea toxicity, due to poor mixing of feed or to errors in calculating the amount of urea to add to the ration. This paper aims to summarize some of the results of research on the benefits and possible negative effects of urea use as supplement to ruminants feed.